Shifting between cultural identities: The voice of preschool children - Popa, Maria Cristina (Journal of Education Culture and Society, 2018)
Aim. The purpose of this research is to capture the shift between two cultural identities, for a group of Romanian children enrolled in a German teaching preschool class, and to closely analyze the impact on cultural identity components. Methods. In this study 27 children, aged 3 to 6, were involved, together with their parents and two teachers. During one year of investigation, they were analyzed using participative observation, focus groups and in-depth interviews conducted in a public preschool. Results. The analysis reveals witch cultural identity components of this children undergo transformation, in what amount and with what impact considering the school environment and the influence of both parents and teachers. For this research, the exploration of cultural identity components was done under the conceptualization proposed by Ching Wan and Pony Yuen-Ga Chew (2013), namely: cultural knowledge, categorization and social relationships (the self-expressed in attitudes and behaviors). Conclusions. Although a positive image emerges for the German culture as a future culture of belonging, we notice the children’s effort to achieve the cultural shift desired by their parents and an emotional subtle discharge in their free play and verbalized mental models. The different vision of parents and teachers over education strengthens some components of cultural identity by broadening the autonomy-shame ambitus that increases the level of self-confidence, which receives a distinct German cultural mark.